10 - Strategies and Outcomes of Involving University Students in Community Engagement: An Adaptive Leadership Perspective - Tsotetsi, Cias T.; Preece, Julia; Manicom, Desiree; Hlalele, Dipane (Journal of Higher Education in Africa, 2022)
The purpose of this article is to compare how students and community members learned and applied their knowledge in four small-scale univer- sity–community engagement projects during 2013. It draws on the concept of adaptive leadership as an approach and analytical tool in a recently com- pleted community engagement and service learning action research partner- ship between the University of the Free State (UFS) Qwa Qwa campus and the University of KwaZulu-Natal (UKZN) Pietermaritzburg campus. The project was funded by the National Research Foundation, with additional support from the UKZN Teaching and Learning Fund and UFS Faculty of Education research funds. A total of twelve case studies involved sixty-five students, nine NGOs and four schools. In each case, students worked in teams in response to community requests for assistance. Projects included Saturday curriculum activities for schools, workshops for parents, assisting with film making or archiving, assisting with monitoring and evaluation of rural reading clubs, producing small organic gardens and assisting with a childcare development project. Each case study involved end of project interviews with students and community contacts and some interim ob- servations during the project implementation phase. This article compares four of the case study findings between the two institutions. It outlines how the concept of community engagement has evolved and briefly reviews the literature on community engagement, particularly in the South African context. It then introduces the theoretical framework and methodology. The findings suggested that the adaptive leadership approach contributed to stimulating shared ownership of learning.